Exporting to the European Community under the Lome IV Convention: the trade cooperation arrangements including the Rules of Origin explained (CARICOM Export Development Project St. MichaelBB, 1993)
Looks at various aspects of the trade co-operation arrangements viz. the contracting parties to the convention; non-independent overseas countries and territories; ACP-EEC trade co-operation; the rules for determining what are ACP originating products; scope for derogations from the origin criteria; some examples of the working or processing requirements for establishing ACP originating status; documentary evidence of origin; verification of evidence of origin; and review of the origin rules provisions.
DC